Faktor-Faktor Yang Berhubungan Dengan Pernikahan Usia Dini Pada Remaja Putri Di Kecamatan Tambusai Utara Kabupaten Rokan Hulu - Handayani, Eka Yuli (Jurnal Martenity and Neonatal, 2014)
Early marriage is a marriage under the age of 20 years of reproductive age in women and less than 25 years in men. Data from the Office of Religious Affairs Tambusai Northern District of Rokan Hulu in 2013 of 535 marriages there were 188 (35%) of married women under the age of 20 years. This study aimed to known factors associated with early marriage, namely knowledge, environment, family income, parental education, youth education, and occupation of parents. This study is a quantitative analytical cross-sectional study design types. The population in this study was 535 with a sample of 210 people were taken by means of systematic random sampling. Data analysis was performed using univariate, bivariate and multivariate chi square test with multiple logistic regression. The results of this study are, parents Occupation: pvalue 0.012 and POR 7 (95% CI = 1.65 to 32.8), Education teenage daughter: pvalue 0.001 and POR 5 (95% CI = 2.68 to 10.75) , Knowledge: POR pvalue 0.019 and 2.3 (95% CI = 1.14 to 4.48) Environment: POR pvalue 0.027 and 2.1 (95% CI = 1.01 to 4.03). The conclusion of this study is that there is relationship between knowledge, environment, youth education and employment of parents with early marriage. Advice for health workers in order to increase the knowledge of youth and families about adolescent reproductive health in the form of counseling, IEC through the media, and PIK-KRR in school.